2012
DOI: 10.1016/j.physletb.2012.07.023
|View full text |Cite
|
Sign up to set email alerts
|

A new formulation to calculate general HFB matrix elements through the Pfaffian

Abstract: A new formula is presented for the calculation of matrix elements between multi-quasiparticle Hartree-Fock-Bogoliubov (HFB) states. The formula is expressed in terms of the Pfaffian, and is derived by using the Fermion coherent states with Grassmann numbers. It turns out that the formula corresponds to an extension of generalized Wick's theorem and simplifies the combinatorial complexity resulting from practical applications of generalized Wick's theorem by unifying the transition density and the transition pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…Many theoretical works followed Robledo's pioneering work [5][6][7][8][9] in order to extend Robledo's formula to multiple quasiparticle excited states. The extension essentially corresponds to finding a formula to evaluate a quantity such as…”
Section: The Pfaffian Formulaementioning
confidence: 99%
See 2 more Smart Citations
“…Many theoretical works followed Robledo's pioneering work [5][6][7][8][9] in order to extend Robledo's formula to multiple quasiparticle excited states. The extension essentially corresponds to finding a formula to evaluate a quantity such as…”
Section: The Pfaffian Formulaementioning
confidence: 99%
“…(11) can be evaluated with an aid of the formula derived in [8] to be Pf(X)Pf(X −1 { j,i,k,l} ), which was demonstrated explicitly as an example in Eq. (46) of Ref.…”
Section: An Application Of the Pfaffian Formulae: Calculation Of ĥmentioning
confidence: 99%
See 1 more Smart Citation
“…His proof is mathematically very elegant and interesting [5]. Moreover, these techniques led us to a relation to the generalized Wick's theorem and its related topics [9], [10], [11], [12], [13]. The proof by Robledo is, however, rather abstract and it somewhat keeps us from an intuitive understanding of the reason for the disappearance of the sign ambiguity.…”
Section: Introductionmentioning
confidence: 99%
“…In nuclear structure physics, the Pfaffian concept has been introduced [9] as a key mathematical tool for solving the long-standing problem in the phase determination of the Onishi formula [10]. Moreover, it has been shown that the Pfaffian algorithm is very efficient also for calculating overlap matrix elements [11][12][13][14][15][16]. In particular, by means of Fermion coherent states and the Grassmann integral, one can derive an alternative approach to calculate the rotated matrix element for general qp states [17], which serves as a theoretical framework to extend the PSM model space [18].…”
Section: Introductionmentioning
confidence: 99%